2011
DOI: 10.1097/shk.0b013e3181f48942
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Imipenem and TAK-242, a Toll-Like Receptor 4 Signal Transduction Inhibitor, Improves Survival in a Murine Model of Polymicrobial Sepsis

Abstract: Sepsis is characterized by an excessive host response to infection. Toll-like receptors (TLRs) are essential for triggering this type of host immune response. Toll-like receptor 4 mediates recognition of LPS from gram-negative bacteria and is an important initiator of sepsis. In the present study, we evaluated the efficacy of TAK-242, a novel TLR4 signal transduction inhibitor, in a murine cecal ligation and puncture (CLP) model. Treatment with TAK-242 (10 mg/kg i.v.) in combination with imipenem (1 mg/kg s.c.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…Our results are in agreement with earlier studies (Camara-Lemarroy et al, 2015). The results are also similar to earlier studies using imipenem and TAK-242, a toll-like receptor4 inhibitor (Sha et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
“…Our results are in agreement with earlier studies (Camara-Lemarroy et al, 2015). The results are also similar to earlier studies using imipenem and TAK-242, a toll-like receptor4 inhibitor (Sha et al, 2011). …”
Section: Discussionsupporting
confidence: 91%
“…Inflammation, tissue damage, and lethality are diminished in the absence of TLR4 signaling (29). However, in the setting of infection with live bacteria, the contribution of TLR4 varies depending on the experimental model and type of organism used in the study (13)(14)(15)(30)(31)(32)(33)(34)(35)(36)(37). Most early studies used mouse strains with mutant forms of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…When LPS binds to TLR4, an inflammatory response is initiated via production and release of cytokines as well as stimulation of inflammatory cells [11]. Targeting TLR4 with antibodies or specific inhibitors has shown beneficial effects by reducing mortality in experimental models of Gram-negative sepsis [12][13][14][15][16][17]. Initial clinical trials also showed beneficial effects of blocking TLR4 in sepsis [18], but in larger follow-up investigations, survival was not improved [19,20].…”
Section: Introductionmentioning
confidence: 99%